Social media detoxification among generations Y and Z in Sleman Regency, D.I. Yogyakarta Province - Balqis, Darin Rania; Rahayu (Program Studi Ilmu Komunikasi, 2025)
This study aims to explore the social media detoxification practices undertaken by Generation Y and Z in Sleman Regency, Yogyakarta, through an exploratory survey of 153 respondents. Drawing on the theoretical frameworks of Franks et al., Soliman & Rinta-Kahila, and Nguyen, this study examines the motivations, challenges, benefits, and strategies associated with detox behavior. Findings suggest that detox practices from both generations are driven by internal motivations, particularly due to stress and excessive use. However, Generation Z experiences more substantial emotional and social challenges, such as FOMO and social judgment. Interestingly, even though Generation Z detoxes more frequently, Generation Y tends to do so for a longer duration. This research also found that both generations generally detox temporarily, especially from Instagram, by deleting the application or deactivating the account. This study contributes to the research on digital detox in Indonesia by providing a comparative analysis across generations and integrating several theoretical approaches.